(untitled) (Biological Sciences - PJSIR, 2022)
This paper is based on the distribution pattern and abundance of teraponid species of the family teraponidae from Karachi coast, Pakistan. For this study, 1304 specimens of family teraponidae were collected during January, 2013 to December, 2014 from commercial landings at Karachi Fish harbour. Three species of family teraponidae (Terapon jarbua,T. puta and T. theraps) were investigated from the samples.The frequency distribution pattern of teraponid species was recorded as 51.84% for T. jarbua and 47.70% for T. puta, T. theraps was rarely present in the commercial catch at Karachi coast.